مدى مساهمة المصارف الخاصة العاملة في سورية في الاستثمار الخاص (دراسة من عام 2004-2010 ) - الزرير, رانيا (Latakia University Journal - Economic and Legal Sciences Series, 2014)
دخلت المصارف الخاصة إلى جانب المصارف العامة في سورية ضمن خطة إصلاح شملت النواحي الاقتصادية والمالية، وبما أن المصارف العامة تتولى مهمة تمويل القطاع العام بشكل أساس واستقبال ودائعه، تكون المصارف الخاصة مسؤولة بشكل كبير عن تمويل القطاع الخاص ودفع عجلة الاستثمار في القطاع الخاص وصولا لأهداف التنمية المنشودة، وعلى الرغم من مساهمة المصارف الحكومية في تمويل القطاع الخاص إلا أنها تبقى مقيدة بالتوجهات العامة للسلطات النقدية وتقدم الدعم لمؤسسات الدولة بشكل أساس، لذلك تناول هذا البحث دور المصارف الخاصة في تنمية الاستثمار في القطاع الخاص من خلال أنواع التسهيلات الائتمانية المختلفة التي تقدمها له، وقد توصل البحث لعدم وجود علاقة ذات دلالة معنوية بين مجمل التسهيلات الائتمانية التي تقدمها المصارف الخاصة في سورية وبين حجم الاستثمار الخاص، مما يعني ضعف دور هذه المصارف في زيادة الاستثمارات، وقد قدم الباحث مجموعة من التوصيات التي تساعد على إيجاد الحلول المناسبة. Private banks began to work with public banks in Syria Under an economic and financial reform plan, As the public banks undertake the task of financing the public sector mainly and receive deposits from it, The private banks largely responsible for financing the private sector and increased investment in the private sector to achieve the goals of development, Although the contribution of government banks in the financing of the private sector , but it remains constrained orientations of the monetary authorities and provide support to state institutions, mainly,so, this research studied the role of private banks in the development of investment in the private sector through thevarious types of credit facilities of offered by private banks, we don't found a significant relationship between the credit offered by private banks in Syriaand the size of private investment, which means the weakness of role of these banks to increase investment, the researcher has provided a set of recommendations that will help to find appropriate solutions.